The Performance Improvement of Long Range Inter-relay Wireless Cooperative Network using Three Time Slot TDMA based Protocol - Imranullah, Khan; Tan, Chong Eng (2013)
Time division multiple access (TDMA) amplify and forward based protocols for cooperative wireless networks have been investigated previously by various researchers. However, the analysis for these protocols is not considered for long range cooperative wireless networks over Rician fading channel. Therefore, the aim of this paper was to propose three time slot TDMA based transmission protocol for inter-relay cooperative wireless network with longer distances between source to relays and destination as well as between relays to destination. It is concluded that the proposed protocol shows less BER performance for long range inter-relay cooperative network over Rician fading channel as compared to two time slot long range cooperative network. Moreover, the proposed protocol shows better performance in terms of less BER values when the inter-relay distance is minimum.